Morfometrik Genus Terebellobranchia sp. (Kelas : Polychaeta, Famili: Terebellidae) di Daerah Intertidal Pulau Lemukutan, Kabupaten Bengkayang - Tri Rima Setyawati, Heru Winarko Junardi (Jurnal Protobiont, 2019)
Terebellobranchia sp. is a member of the Terebellidae family, which is known to have a high level of morphological variation. The aims of research was to know morphometric variations and the relationship of body size and uncini of Terebellobranchia sp. in Lemukutan Island. The measurements body and uncini were carried out on complete specimens with digital caliper, while uncini measuring under a microscope with eyepiece micrometer. Data analysis with t test in 64 individuals. The Terebellobranchia sp. found in station 2 had a significantly different size with Terebellobranchia sp. in other stations. The body length of Terebellobranchia sp. shows a strong correlation with the width, number of segments and body weight, meanwhile the width of the segment strongly correlated with size of uncini.